25 Mitral inflow velocity encoded imaging by CMR for the assessment of left ventricular haemodynamics. (March 2019) - Balasubramanian, Nithin; Barker, Natasha; Fidock, Benjamin; W Macdonald, Alistair; Capener, David; S Johns, Christopher; Karunasaagarar, Kavitasagary; Fent, Graham; Al-Mohammad, Abdallah; Rothman, Alexander; G Kiely, David; M Wild, James; et al.
Abstract : Background: Heart failure is common and is associated with high mortality and morbidity. Haemodynamic assessment is critical to diagnosis and therapeutic monitoring. Non-invasive Doppler echocardiography is commonly used to assess peak early and late mitral inflow velocities to predict left ventricular (LV) haemodynamics. Cardiovascular magnetic resonance imaging offers two-dimensional through plane flow assessment using phase contrast acquisition. It remains unclear which through plane mitral inflow velocity (averaged or peak) best predicts LV haemodynamics better. Purpose: The objective of this study is to investigate which through plane mitral inflow velocities (averaged or peak) is better associated with invasive left heart haemodynamic parameters. Methods: In this observational study, 16 patients were prospectively recruited at a large tertiary pulmonary hypertension unit. These patients had invasive right heart haemodynamic catheter-based study (RHC). In addition, all patients received CMR on the 1.5 T scanner (HDx scanner, GE Healthcare, Waukesha, Wisconsin, USA), using an 8-channel cardiac coil. CMR protocol included long and short axis cines and mitral inflow phase contrast acquisition. The LV haemodynamic parameters assessed by RHC included the following: pulmonary capillary wedge pressure (PCWP), cardiac output, cardiac index, systemic vascular resistance (SVR). Cardiac output assessment was done by standard thermodilution method. Results: Mean age of the 16 patients analysed was 68.7±7.9 years and 56.3% were female. Of the 16 patients, 5 patients had non-analysable data. Mean PCWP was 11.1±4.7 mmHg, mean cardiac output was 4.4±1.3 L/min, mean cardiac index was 2.4±0.8 L/min/m 2 and mean SVR was 1827±589 dynes/seconds/cm -5 . Peak EA ratio correlated with PCWP (r=0.68 p=0.02) and with cardiac index (r=0.68 p=0.02). There was a notable correlation between mean EA ratio and cardiac index (r=0.66 p=0.03). Mean A showed a significant correlation with SVR (r=0.64, p=0.03). Conclusions: Peak mitral inflow velocities are more closely associated with LV haemodynamics. This may be due to reduced variation in through-plane peak velocity at different inflow levels versus the mean velocity. Future work is required to determine the effect of addressing the valvular through-plane motion, which may make the averaged mitral inflow assessment a better tool for LV hemodynamics.